Key Factors Contributing The Success of Informal Sector Business Owners in Makassar - Abdul Rakhman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
The purposes of this research are to investigate the key factors contributed to the informal sector businesses success, how the key factors formed, and how unique the key factors contributed to daily profit. The research was undertaken in Makassar City, South Sulawesi, Indonesia by asking 450 respondents using listed Indicators mentioned in questionnaires, observing the informal sector businesses in several streets in Makassar and asking the participants to list the important indicators which are believed to be important in making informal sector business success. The collected data were analyzed using multidimensional scaling analysis to classify the class of indicators. The research concluded that there were several aspects contributed to the success of informal sector businesses. Firstly, the use of equity is the most important indicator in financial aspect, the owners tended to refuse the use of debt. Secondly, in environment aspect, the owners identified that choosing good place, approval place by the government, neighbor skills watching, be aware of removal by the taskforce, training and technical support and keeping in touch with current technology were very important. Thirdly, the marketing aspect. the respondents emphasized in service quality, the quality of the product or services and performed the special treatment to customers in order to achieve the success. However the informal sector did not over service guarantee and did not believe that selling other owners' product could contribute to success of the business.